Cytotoxicity and Identification of Active Compounds in Sea Urchas (Diadema Setosum) in the Waters of Sinar Hading Village - Liwun, Maximus Gawa; Batafor, Yosephina M. J.; Peni, Donata (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Indonesia boasts a rich marine biodiversity, including approximately 950 species of sea urchins, 84 species belonging to 48 genera and 21 species, found in Indonesian waters. This study aimed to determine the cytotoxicity level and identify active compounds in sea urchins (Diadema setosum) obtained from the waters of Sinar Hading Village, Lewolema District, East Flores Regency. The cytotoxicity test was conducted using the Brine Shrimp Lethality Test (BSLT) method with Artemia salina larvae. Identification of active compounds was performed using Gas Chromatography-Mass Spectrometry (GC-MS). The results showed that the sea urchin extract had an LC50 value of 94.51 ppm, which is considered moderately toxic. GC-MS analysis identified several active compounds, including trichloroethylene (3.9%), dimethyl disulfide (14.97%), toluene (100%), ethene 1,1,2,2-tetrachloro (25.54%), and several other toxic organochlorine compounds. These findings indicate that Diadema setosum has potential as a source of bioactive compounds for use in pharmaceuticals and biotechnology.